ELECTROCHEMICAL AND CHEMOMETRIC DETERMINATION OF DORZOLAMIDE AND TIMOLOL IN EYE DROPS USING MODIFIED MULTIWALL CARBON NANOTUBE ELECTRODE - Hendawy, Hassan A.m.; Elwy, Hanan M.; Fekry, Amany M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This work is focused on the construction of simple and sensitiveÂ electrochemical sensor for quantitative determination of dorzolamide (DOR) and timolol maleate (TIM). This method is based on the incorporation of multiwall carbon nanotubes (MWCNT) into the carbon paste electrode which improve the characteristics of the electrode. Methods: The electrochemical response of modified electrode was based on voltammetric oxidation, using cyclic voltammetry (CV) and impedance spectroscopy (EIS). The structural morphology of the surface modified electrode was characterized by scanning electron microscope (SEM). Quantitative analysis for each of the two compounds in a mixture has been examined by using of chemometric tools for resolving overlapping signals. The prediction performance of the chemometric method was analyzed by principal component regression (PCR) and partial least square (PLS). Results: Fractional factorial design was constructed from set of synthetic mixtures of two drugs in concentration ranges of 0.05 to 1.6Âµg/ml for DOR and 1.5-20 Âµg/ml for TIM. Under optimum experimental conditions, DOR and TIM gave rectilinear response over the concentration range of 0.072-1.88 Âµg/ml and 1.16-20.84 Âµg/ml, respectively. The limit of detection (LOD) was found to be 0.098 and 1.025 Âµg/ml, for DOR and TIM, respectively. It found that the % of relative prediction error (RPE) was acceptable and satisfactory. Conclusion: In these work, for the first time, a new voltammetric simultaneous method developed for a rapid and efficient determination of DOR and TIM from eye dropper sample at nano modified electrode with satisfactory results. These results indicate that MWCNT holds great promise in practical application.